(untitled) (Indian Journal of Arid Horticulture, 2025)
Xeriscape is a systematic concept for saving water in landscaped areas. Xeriscaping (zer-i-skaping) is a word originally coined by a special task force of the Denver Water Department, Associated Landscape Contractors of Colorado and Colorado State University, USA to describe landscaping with water conservation as a major objective. Even though dry-only landscaping can be quite spectacularly colorful, and even lush, limited areas of more highly watered landscape are completely consistent with wise water use. There are vast arrays of wonderful plants indigenous to all regions, non-invasive introduced plants, that are well adapted to the local regional climate, are wonderful additions to landscaping that uses water frugally. Xeriscape is not necessarily a lawn less landscaping. Some lawns, even of species that are more highly watered, can be consistent with wise water use. "Less-lawn landscaping," rather than "Lawn-less landscaping" is an appropriate statement. On the contrary, well planned Xeriscapes are splendid examples of beauty and diversity.